2012
DOI: 10.1177/1524839912460871
|View full text |Cite
|
Sign up to set email alerts
|

Stage of Change and Other Predictors of Participant Retention in a Behavioral Weight Management Program in Primary Care

Abstract: High attrition often limits the efficacy of weight management programs, particularly those that serve primary care patients. We investigated stage of change and other predictors of retention in a behavioral intervention program that enrolled adult obese patients at three primary care sites. The program included practice improvements and provider training, as well as individual lifestyle counseling and educational group classes for participants. We analyzed predictors of whether participants returned for counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 29 publications
(76 reference statements)
1
49
0
1
Order By: Relevance
“…Sixty-eight percent of men agreed strongly that they delay/avoid visiting a doctor at least some of the time. As reported in other studies [31, 32], work and family commitments were common reasons for delaying doctor’s visits, and expectedly, young healthy men rated these as reasons more strongly than young sick and older men. Not only were younger men more likely to self-monitor than older men, but those who scored higher on delay/avoidance behaviour, reported a higher likelihood of attending a DMHS.…”
Section: Discussionsupporting
confidence: 67%
“…Sixty-eight percent of men agreed strongly that they delay/avoid visiting a doctor at least some of the time. As reported in other studies [31, 32], work and family commitments were common reasons for delaying doctor’s visits, and expectedly, young healthy men rated these as reasons more strongly than young sick and older men. Not only were younger men more likely to self-monitor than older men, but those who scored higher on delay/avoidance behaviour, reported a higher likelihood of attending a DMHS.…”
Section: Discussionsupporting
confidence: 67%
“…10,11 Previous research has identified that program characteristics (such as frequency of contact), healthy behaviour changes made during the program, the participant's health status, lack of motivation and life events during program engagement can all influence participant retention and withdrawal. [12][13][14] It is important to understand the contributing factors that make a health coaching program appealing and engaging for some, but not for others. Elaborating on the reasons for attrition from the GHS will inform ongoing service improvement and future 'real-world' programs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, teaching and wisdom for the young people the way to conduct themselves in the community circle, especially personal; cognitive; behavior; psychological; moral; social and spiritual. At the same time, the leader employs the opportunity to conduct general counseling for those who have problems (Toth-Capelli et al, 2013;Mistry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The culture was a historically transmitted pattern of meanings embodied in symbols. Soares et al, (2017) confirm Eleganaboi is one of most classical ceremony existed among Luro society. This conducted in the group by six and more adolescent, adult or elderly people.…”
Section: Introductionmentioning
confidence: 99%